Romanian state policy regarding minorities and civil liberties after 1990. Security aspects - Bocai, Adina Elena (Technium Business and Management, 2023)
With its post-1989 policy on national minorities, Romania is considered by Western capitals a successful model. For more than 30 years, Romania has constantly harmonised its policies regarding the national minorities with the historical factor on the one hand, and with the provisions of the international organisations to which it has become a part on the other, cultivating historical and ethnic values within a well-defined framework, not only from a historical and cultural point of view, but also from a legal perspective. Currently, 20 national minorities are officially recognised in Romania, represented in parliament by 19 organisations. This article aims to highlight the generous legislation regarding national minorities in Romania and to launch a new approach, namely the security approach. The theoretical framework proposed for this article consists of two fundamental theories designed to support the placement of the field of national minorities in Romania within a security framework: the five dimensions of security theory, as presented in the seminal works of the Copenhagen school of thought, in particular in Barry Buzan’s Peoples, states and fear (1991) and in Security. A new framework for analysis by Barry Buzan, Ole Waever and Jaap de Wilde (1998) and the theory of the triadic national minority-host state-motherland relationship by professor Rogers Brubaker (1996).